Meningkatkan Aktivitas Kolaboratif dan Pemahaman Konsep Mahasiswa pada Perkuliahan Fisika Dasar I melalui Lesson Study - Wayan Suana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2016)
This study aimed to increase students’s collaborative activity and conceptual understanding in Fundamental Physics I course through the implementation of lesson study in two parallel classes. Each lesson study cycle consisted of three stages, started with planning a lesson, teaching and observing the lesson, and reflecting the result, for the first class. After that, revising the lesson plans to be implemented in the second class. The results showed that students’s collaborative activities and conceptual understanding for the two classes increased from cycle I – cycle III. The average scores of first class’ collaborative activity from cycle I - cycle III were 72.0, 75.8, and 81.6, respectively while for the second class were 73.4, 78.8, and 82.6. Moreover, the average conceptual understanding for the first class from cycle I - cycle III were 42.7, 58.8, and 66.2, respectively, while the second class were 48.5, 65.5, and 66.1. The results also showed that the average collaborative activities and understanding the concept of second grade students tended to be better than students of the first class.